Processing of nanocomposites PLA/graphite using a novel elongational mixing device. Issue 1 (13th March 2014) - Ibarra‐Gómez, Rigoberto; Muller, René; Bouquey, Michel; Rondin, Jérôme; Serra, Christophe A.; Hassouna, Fatima; Mouedden, Yamna El; Toniazzo, Valérie; Ruch, David
<x xml:space="preserve">Abstract</x> Expanded graphite (EG) was added to polylactic acid (PLA) and then fully mixed in a novel elongational mixing device (RMX) to obtain PLA/EG nanocomposites. The operation of the new mixer device is based on the induced multiple passages of material (by means of reciprocating pistons) at different flow speeds through a short capillary die, thus creating convergent/divergent elongational flows. Highly homogeneous materials were obtained at all mixing conditions and particle size ranged from hundred to several hundreds of nanometers. Also, X‐ray diffractograms showed different intensity of the characteristic peak of EG (3% wt/wt EG was kept constant), suggesting partial exfoliation. Furthermore, the molecular weight of processed neat PLA samples was assessed in order to correlate the PLA degradation to morphology and reinforcement mechanisms in the nanocomposites, as a function of the RMX parameters. As well, final flow properties of neat PLA and EG compounds were obtained by dynamic rheology. Thermo‐mechanical degradation of PLA was found to play a major role in the rheology of mixing. On the other hand, PLA nanocomposites presented a storage modulus between 20 and 40% higher than neat PLA. Finally, morphology comparison between the RMX and an internal mixer, at the same mixing energy input, demonstrated a higher dispersive mixing efficiency for the RMX. POLYM. ENG. SCI., 55:214–222, 2015. © 2014 Society of Plastics Engineers